School Operational Effectiveness Analysis Web Based Event System with Dynamic Systems Development - Sama, Hendi (Universitas Medan Area, 2019)
School institutions in Batam have problems in how the events they conduct can support the school's operational effectiveness. The solution model for these problems is to build web-based event systems using the dynamic systems development (DSDM) method. This system aims to solve problems that occur in event scheduling at activities carried out at school institutions in Batam. The school representative used is a school in Batam. The method is done by learning and the feasibility of case studies, model functionality, design, and implementation. This implementation produces a system that is very helpful in processing data and reports during the event. Starting from the registration of the event, the continuity of the event, until the completion of the event, all can be stored in detail. Besides users, there are also managers and administrators. Managers have a role to manage the data entered by registrants, while administrators give access to each user account and maintain system security. This system is divided into 2 roles with one as a user and one acting as an administrator. Registrants to participate in this event act as users. The results of this study are that school operational effectiveness increases after implementing this web-based event system.